Professional development of secondary school EFL teachers: Voices from Indonesia. (October 2019) - Cirocki, Andrzej; Farrell, Thomas S.C.
Abstract: Continuing professional development (CPD) means that language teachers need to keep updating their knowledge and skills continuously throughout their careers. This paper reports on a study of the CPD experiences of 250 teachers of English as a foreign language (EFL) in secondary schools in Indonesia. Using a mixed-methods approach – through the use of a questionnaire, a reflective report and a focus group interview – the results revealed a detailed picture of the continuing professional development in the context under study. Specifically, the findings indicated that the EFL teachers conceptualise professional development in five different ways: school-based learning, an academic undertaking, a professional pursuit outside the school environment, a government scheme and self-directed learning. The study also showed that although the teachers said that they have ample opportunity to develop professionally, not everyone takes advantage of this. The study additionally reveals that some professional development activities are more impactful than others. Finally, the article recommends steps that seek to help EFL teachers to sustain their continuing professional development as well as offers directions for future research.